Effect of low-level laser therapy on wound healing after gingivectomy - Vikrant Sharma; D S Kalsi; Arushi Goyal; Swantika Chaudhry; Naveen Oberoi; Parvinder Singh Baweja (Wolters Kluwer Medknow Publications, 2021)
Low-level laser therapy (LLLT) is based on the principle of biostimulation or biomodulation effect. LLLT after gingivectomy has resulted in better wound healing because of its action on collagen synthesis, angiogenesis, and growth factor release. The authors here present a case report on the effect of LLLT, using a diode laser (InGaAsP), on wound healing and patient's response after scalpel gingivectomy.